Depression, Resource Utilization, and Outcomes Following Liver Transplant. (September 2016) - Sebaaly, Jamielynn C.; Fleming, James; Pilch, Nicole; Meadows, Holly; Finn, Anastasia; Chavin, Kenneth; Baliga, Prabhakar; Bratton, Charles F.; McGillicuddy, John W.; Nadig, Satish; Taber, David
Context: There is evidence that depression after liver transplant (LTX) is associated with increased morbidity and mortality; however, the effect of depression treatment on LTX outcomes has not been well established. Objective/Setting/Design: This single-center, longitudinal cohort study aimed to determine whether depression treatment influences outcomes after LTX. Depression diagnosis was based on medical history and documentation from psychosocial providers. Patients/Intervention/Main Outcome Measures: Patients were studied from October 2010 to June 2013 and separated into 3 groups for analysis: no depression, adequately treated depression, and inadequately treated depression. Adequacy of depression treatment was determined using the Antidepressant Treatment History Form. Results: Of the 161 patients included in the analysis, 103 did not have depression, 24 had adequately treated depression, and 34 had inadequately treated depression. Baseline demographics were similar between the groups. Patients with inadequately treated depression had significantly more encounters with a health-care provider ( P = .03). Graft loss tended to be higher in these patients (27% in the inadequately treated group, 17% in the adequately treated, and 14% in the no depression group, P = .25). The adequately treated group was more likely than the inadequately treated group to be on antidepressants at 30 days post-LTX ( P = .001). The inadequately treated group was more likely to be on a sleep aid 30 days post-LTX ( P = .01). Conclusion: Inadequately treated depression led to increased health-care resource utilization. Patients with adequately treated depression had similar outcomes as those with no depression. Use of sleep aids early post-LTX may be a surrogate indicator of inadequately treated depression.